A LOOK AT THE GENESIS OF WORKS CREATED WITH ALLEGORICAL CONTENT - Bilolkhon Khamitjonovich Abdullayev (Journals Park Publishing, 2025)
In this article discussed about the genesis of works of the type of bird discussion created in the Turkish language tradition. In addition, the reasons for the similarity of the form and content of these types of works; the interaction of the works, as well as the peculiarities of their creation, will be briefly discussed. Along with this, the issues of tradition and followership in the creation of figurative masnaviy are also dealt with in detail.